The Effect of Overconfidence Behavior on Investment Decision-Making Among Indonesian Investors - Khoirunnisa Virgiana Khan; Hesti Juni Thalia; Afina Medina Azaleya (Jurnal Sosial Sains dan Komunikasi, 2026)
Investment decision-making plays a crucial role in achieving optimal financial outcomes. However, investors frequently make irrational decisions due to psychological biases, one of which is overconfidence behavior. This study aims to empirically examine the effect of overconfidence behavior on investment decision-making among Indonesian investors. A quantitative research approach with an explanatory design was employed. Data were collected through an online questionnaire distributed to 52 investors selected using purposive sampling. The research instruments consisted of a six-item Overconfidence Behavior scale and a twelve-item Investment Decision-Making scale measured using a five-point Likert scale. Data were analyzed using descriptive statistics, reliability testing, normality testing, and simple linear regression analysis with IBM SPSS Statistics 24. The findings reveal that the measurement instruments are reliable, with Cronbach's Alpha values of 0.809 and 0.914, respectively, and that the data satisfy the normality assumption. Hypothesis testing indicates that overconfidence behavior has a significant positive effect on investment decision-making (F = 49.141; p < 0.001). The coefficient of determination (R² = 0.496) demonstrates that overconfidence behavior explains 49.6% of the variance in investment decision-making, while the remaining 50.4% is influenced by other factors. These findings support Behavioral Finance Theory by confirming that psychological biases significantly influence investment decisions and suggest that investors should balance self-confidence with objective financial analysis and comprehensive risk assessment.